The Influence of Oketani Massage on Increasing Breast Milk Production in Post Partum Women in The Working Area of The Tanjung Uncang Community Health Center - Putri, Mona Rahayu; Philip, Rofiqo Larasati; Amru, Desi Ernita; Radulima, Larince (Nusantara Science and Technology Proceedings, 2024)
Breast milk is a mixture of fat within a solution of protein, lactose, and inorganic salts produced by the mother's mammary glands post-delivery as nourishment for the baby. According to the scientific perspective, exclusive breastfeeding helps prevent infant mortality, decrease the incidence of illness, boost immunity, lower allergy risks, promote growth and development, enhance cognitive skills, and offer emotional bonding. Breastfeeding is regularly ruined by different issues experienced by the mother, such as deficient breast drain generation, breast boil, mastitis, breast engorgement, areola issues, and blocked drain channels. The Effect of Oke Tani Massage on Increasing Breast Milk Production in Postpartum Women in the Tanjung Uncang Community Health Center. This type of research is Quasi-Experimental Research with a Pretest post-test nonequivalent Control Group Design, namely by comparing breast milk production in 12 postpartum mothers in the experimental group and 12 postpartum mothers in the control group. In the experimental group, oke tani massage treatment will be given. The results of the independent sample T-test statistical test show a Sig value. (2-tailed) 0.001 < 0.05 means that there is an influence of Oke Tani Massage on increasing breast milk in postpartum mothers in the Tanjung Uncang Community Health Center working area, Batam City. The recommendations from this study offer a safe and effective option for boosting breast milk supply in postpartum mothers and can be explored by anyone.